An Intraoperative Template Technique for Hemi-Hamate Bone Grafts in Reconstruction of the Proximal Interphalangeal Joint - Nikkhah, Dariush; Rawlins, Jeremy; Miller, Robert; Fitzgerald, Edmund (Journal of Hand and Microsurgery, 2019)
The surgical management of proximal interphalangeal joint fracture subluxations is challenging. The hemi-hamate autograft is a useful but technically challenging technique for these injuries. We describe a simple technical note, using a bone wax template to help guide the harvest of a geometrically accurate hemi-hamate graft to facilitate accurate proximal interphalangeal joint reconstruction, while reducing donor site morbidity.
Keywords: hemi-hamate graft; bone wax template; PIPJ fracture subluxation